Development of compress air transportation (CAT) for alternative energy utilization - Mohd Dzulqarnain, Ahmad Suhaimi (2007)
Compress Air Transportation (CAT) is a new concept of transportation that utilizes air as the source of energy. Work on alternative power system for vehicle is becoming very important for the future due to combination of high prices on fuel, emission factor and also the source of the current energy will eventually run out. Several advantages for utilizing air as the source of energy compared to other alternative energy sources makes it become the subject for this project. In this project, a simple transportation utilizing air as the source of energy has been developed. The main component of the engine of the CAT is a device called the "Air Impact Wrench" which can be purchased from local stores. The CAT was tested and analyzed for further studies on expanding this new technology.